Pengaruh Pemberian Kredit terhadap Return On Asset pada PT. Bank Rakyat Indonesia (Persero), Tbk Cabang Pondok Aren Periode Tahun 2010-2019 - Jamaluddin Ali; Mujahidin Mujahidin (Prodi Akuntansi STIE Hidayatullah Depok, 2021)
This study aims to determine the effect of Lending on Return On Assets at PT. Bank Rakyat Indonesia (Persero), Tbk Pondok Aren Branch. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, the variable of credit provision obtained an average value of 406.387 billion%. The return on assets variable obtained an average value of 5.403 %%. Lending has a positive and significant effect on Return On Assets with a regression equation value of Y = 2.254 + 0.008X, and a correlation coefficient value of 0.775 or has a strong level of relationship with a determination value of 60.0%. Hypothesis testing obtained a significance of 0.000 <0.05.